1986
DOI: 10.1159/000215355
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Heparin Treatment of Deep Venous Thrombosis: A Comparison of Unfractionated and Low Molecular Weight Heparin

Abstract: In a double-blind study, patients with phlebographically proven deep venous thrombosis (DVT) were treated with subcutanous injections twice a day of either unfractionated heparin (UH; n = 27) or low molecular weight heparin (LH; n = 29) for 7 days, and the dose was adjusted until therapeutic range was reached, according to a chromogenic substrate anti-Xa assay. Forty-eight percent of the LH group did not need dose adjustment as compared to 24% of the UH group. During the course of heparin administration, devia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(67 citation statements)
references
References 16 publications
(17 reference statements)
1
65
0
Order By: Relevance
“…A number of trials have compared the efficacy and safety of UFH with LMWHs, the primary outcome measure being a change in the size of the thrombus assessed by phlebography approximately 1 or 2 weeks after initiation of therapy. [1][2][3][4][5][6][7][8][9][10][11] In recent large-scale trials, the primary outcome measure was symptomatic recurrent venous thromboembolism in patients treated with subcutaneous LMWH either hospitalized 12 or at home. 12,14 In none of these trials have blood studies been performed to determine whether treatment was effective in controlling the hypercoagulable state associated with the acute phase of venous thromboembolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of trials have compared the efficacy and safety of UFH with LMWHs, the primary outcome measure being a change in the size of the thrombus assessed by phlebography approximately 1 or 2 weeks after initiation of therapy. [1][2][3][4][5][6][7][8][9][10][11] In recent large-scale trials, the primary outcome measure was symptomatic recurrent venous thromboembolism in patients treated with subcutaneous LMWH either hospitalized 12 or at home. 12,14 In none of these trials have blood studies been performed to determine whether treatment was effective in controlling the hypercoagulable state associated with the acute phase of venous thromboembolism.…”
Section: Discussionmentioning
confidence: 99%
“…The results of these trials in general indicate that LMWHs are at least as effective and safe in treating acute DVT as UFH. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] The majority of reported studies do not provide information regarding the effect of therapy on regression of thrombi because second phlebography after treatment was performed only in selected patients who developed symptomatic recurrence. [12][13][14][15] Furthermore, in none of these trials, were blood studies, using markers of in vivo thrombin generation, performed to see if both treatments were equally effective in neutralizing and inhibiting further thrombin generation.…”
Section: Introductionmentioning
confidence: 99%
“…Use of heparins in the treatment of PE and DVT is standard practice and has been subject to refinement over the last half-century, since the key report that UH (albeit in combination with a vitamin K antagonist), compared with no anticoagulant treatment, reduced death and recurrence of thrombosis in a small trial of patients with symptomatic PE (Barritt and Jordan, 1960). Once it had been demonstrated that fixed-dose regimens using LMWH, without the same need for routine monitoring, were as safe as treatment with UH with dose adjustment (based on results of plasma coagulation assays) for DVT (Holm et al, 1986;Prandoni et al, 1992) and PE (Bratt et al, 1985;Hull et al, 1992;Théry et al, 1992), the way was paved for the replacement of UH with LMWH to a large extent. After confirmation of efficacy and safety in larger clinical studies (Dalen, 2002b), LMWH treatment is now the preferred approach in the initial management of VTE (Garcia et al, 2012;Kearon et al, 2012;Cohen et al, 2014) and is used routinely in cases of PE or proximal DVT.…”
Section: Clinical Use As An Anticoagulant/ Antithromboticmentioning
confidence: 99%
“…[17][18][19][20] We contacted the authors of the remaining 19 articles to request cancer subgroup data: One author provided us with the data 21 ; another author indicated that the data were not available anymore 22 ; we used the cancer subgroup data for 7 articles, 23-29 because they were reported in 2 published systematic reviews 5,8 ; and we were not able to obtain any outcome data for the remaining studies. [30][31][32][33][34][35][36][37][38][39] Thus, of 24 studies with cancer patients' subgroups, we were able to obtain data for 13 studies. Agreement between authors for study eligibility was excellent (kappa of 0.94).…”
Section: Data Synthesis and Analysismentioning
confidence: 99%